(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
The plane wave least-squares method combined with local spectral finite elements has been used effectively to solve time-harmonic acoustic and electromagnetic wave propagation with complex wavenumbers. We develop the plane wave least-squares method and the ultra weak variational formulation for the nonhomogeneous case of the electromagnetic wave propagation in anisotropic media. We derive error estimates of the approximation solutions generated by these methods in one special case of TE mode scattering. Numerical results indicate that the resulting approximate solutions generated by these two methods possess high accuracy and verify the validity of the theoretical results.